Analisis Kesalahan Siswa dalam Menyelesaikan Soal Materi Barisan dan Deret Ditinjau dari Komunikasi Matematika pada Kelas IX di SMP Muhammadiyah 2 Kartasura Tahun 2016/2017 - Widyatari, Rina, Dr. Sumardi, M.Si (2017)
The purpose of this study is to describe errors and the cause of student's errors in completing issue of sequences and series term of mathematics communication. The type of this research is descriptive qualitative. The subjects were students of class IX Muhammadiyah 2 Kartasura. Data collection methods used were a test, interview, documentation and observation. Data analysis techniques through Data Reduction, Data Display, and Conclusion. In research's used three indicator of mathematics communication among others stated a daily occurrence in the language or symbols or construct a mathematical model of an event (first indicator). The students able do allegation (second indicator), student able do operation math (third indicator). Errors made by students in solving that is wrong in the data symbolize that known, write down what that asked, set formula, calculate the data prerequisite, student didn't write the formula, entering known data, and sort of mathematical operation. The cause of errors made by students are not accustomed to writing don't what is known and asked, can't remember formulas in the sequence and series, lack of exercise for story problems, and don't recheck the answer.